(untitled) (CIPEEX, 2025)
The quality of life (QoL) of civil servants, teachers, and administrative staff in the Brazilian federal education network is a determining factor for individual well-being and institutional efficiency. This study is a cross-sectional epidemiological study that aimed to evaluate the factors that influence the QoL of civil servants in the Brazilian federal education network. We used the WHOQOL-bref instruments in association with a sociodemographic questionnaire. This study was conducted in 2022, involving 1,563 administrative staff and teachers from the Brazilian federal education network. The approach adopted was cross-sectional and epidemiological in nature. For statistical analysis, we used the Student’s t-test and analysis of variance (2-way ANOVA), followed by post hoc analysis (Tukey) for three or more factors (α=0.05). Teachers reported better QoL in environmental terms when compared to administrative technicians (p<0.001). Men reported better QoL in the physical (p<0.001) and psychological (p<0.001) domains than women. The South region had the best QoL reference in the physical domain (p=0.014), while the Midwest stood out in the environmental domain (p<0.001). The results indicate significant differences in QoL among employees of the Brazilian Federal Education Network. Teachers reported better QoL compared to administrative staff, while men had higher scores in the physical and psychological domains than women. Regional variations were observed, with the South region leading in the physical domain and the Midwest in the environmental domain.